Corporate Performance Measurement Balanced Scorecard Through Approximation Sustainability at Pabrik Gula Krebet Baru Malang - Utoyo, Utoyo; Soeparman, Sudjito; Astuti, Murti (Rekayasa Mesin, 2010)
PG. Krebet Baru consists unit I/II be sugar industrial company with capacity 11.500 tcd, in this time PG.Krebet Baru cope to fulfil national sugar need only seen from ability reachess profit and tall sale level for that companies to want watchfulness aim correct performance measurement system to analyze performance with concept sustainability balanced scorecard that be method development balanced scorecard with add social environment aspect, because this aspect is very krusial to PG. Krebet Baru that presents citizen solid intermediate and, to achieve aim, used several methods AHP and OMAX also detect point of view, mission, target stipulating with performance measurement from each perspective. for researcher activity support submits kuisioner to customer 25 respondents, employee 25 respondents and 2 leadership respondents PG. Krebet Baru and PG.Candi Baru Sidoarjo. kuisioner used to measures /employee customer satisfaction with stipulating KPI complete the heavy, result kuisioner at validity test and realiabilitas. from measurement analysis result is got 30 kpi and 30 sub kpi's as a whole period performance achievement index 2009 performance scores: 7,37 (yellow) mean the performance not yet achieve target, furthermore kpi score 0 until 7 (red/yellow) as much as 27 kpi/sub kpi need repair subsidizes performance as a whole. Keywords : AHP, performance, KPI, OMAX, Sustainability